Pouchitis: a tridimensional view - Sinagra, Emanuele; Raimondo, Dario; Pompei, Giancarlo; Morreale, Gaetano Cristian; Rossi, Francesca; Marasà, Salvatore; Calvaruso, Marco; Mastrocinque, Giuseppe; Mandalà, Stefano; Martorana, Guido; Marchesa, Pier Enrico; Rizzo, Aroldo Gabriele; et al. (Progress in Nutrition, 2016)
The preferred surgical treatment of ulcerative colitis (UC) and familial adenomatous polyposis (FAP) is represented by proctocolectomy with ileal pouch-anal anastomosis (IPAA). However, patients with UC who have undergone IPAA are prone to develop several complications, which include surgery related/mechanical complications; inflammatory or infectious disorders; functional disorders; dysplasia or neoplasia; and systemic or metabolic disorders. Pouchitis, which is defined as the acute and/or chronic inflammation of the ileal reservoir, represents the most common long-term adverse sequela after IPAA. Gut microbiota play a pivotal role in the initiation and disease progression of pouchitis. Pouchitis can be classified according to the activity of the disease, the duration of the symptoms, the pattern of the disease or response to antibiotic therapy. Patients with IPAA for UC tend to experience a variety of symptoms, ranging from mild pelvic or perianal discomfort to a debilitating complex of symptoms that may eventually lead to pouch excision thereby necessitating the construction of a permanent ileostomy. To date, the etiology, the diagnosis and the medical management of pouchitis represent a clinical challenge. In fact pouchitis range from a disease with an acute antibiotic-responsive presentation to a chronic antibiotic-refractory form, with subsequent different disease mechanisms and clinical course. A tridimensional and multidisciplinar approach, including endoscopy, histology, and laboratory testing is widely helpful to identify the different phenotypes of the disease and to manage correctly its treatment.